Ready technology fast-tracking new business technologies - Andriole, Stephen J. (CRC Press, 2015)
Companies understand that their ability to compete is tied directly to their ability to leverage the very latest technology advances. Fortunately, deploying new technology has never been easier, primarily due to early maturity and cloud delivery. One approach that is helping companies rapidly pilot and affordably deploy new technologies is ready technology, a new category of information technology (IT). This book explains the ready technology adoption process in detail, enabling companies to exploit new technology immediately and effectively. In this book, the author challenges the traditional.
Includes bibliographical references (pages 123-125) and index
Keywords: Information technology; Electronic data processing; Technologie de l'information; information technology; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference